Advances in Cotton Research - Ansari, Mahmood-ur-Rahman (IntechOpen, 2020)
Advances in Cotton Research is an interdisciplinary book dealing with diverse topics related to recent developments in cotton improvement. It discusses the latest research in the field of Bt cotton, abiotic stress, strategies to combat various abiotic stresses, the potential use of cotton biomass for bioenergy production as well as factors influencing cotton spinning. This book provides advanced knowledge for cotton breeders, researchers in related fields, students, life science researchers, and interested readers.